The Students' Skills in Solving Mathematics Open-Ended Problems Based on Cognitive Style Backgrounds - Ulya, Putri Syarifatul; Setyaningsih, Nining (Edumatika, 2024)
Differences in students' cognitive styles cause differences in accepting and managing learning and connecting experiences into learning. Differences in students' cognitive styles also cause differences in mathematical problem-solving skills. This research aims to describe students' skills in solving mathematics open-ended problems in terms of differences in cognitive styles, namely Field Independent (FI) and Field Dependent (FD). This research is descriptive qualitative research that involved four eight-grade students at a private junior high school in Sukoharjo, Central Java, Indonesia as subjects who were selected based on differences in cognitive styles. Cognitive style data was collected through a cognitive style questionnaire while students' mathematical problem-solving skills were revealed through tests and interviews. The data was analyzed to identify the fulfillment of indicators of mathematical problem-solving skills according to Polya, which include understanding the problems, preparing plans, implementing plans, and looking back. The results showed that field independent subjects had better mathematical problem solving abilities than field dependent subjects. Field independent subjects fulfill all indicators of mathematical problem-solving skills, while field dependent subjects only fulfill indicators of understanding the problems. This research can be used as a reference in designing learning strategies that suit all students' cognitive styles to improve students' mathematical problem-solving skills.